Using the critical path method to rollout and optimise new PMTCT guidelines to eliminate mother-to-child transmission of HIV in Zimbabwe: a descriptive analysis - Reuben Musarandega; Joanna Robinson; Priti Dave Sen; Anna Hakobyan; Angela Mushavi; Agnes Mahomva; Godfrey Woelk (BMC, 2020)
Abstract Background Achievement of the elimination target for mother-to-child transmission (MTCT) of HIV in selected countries has increased hope to end the HIV epidemic in children across the world. However, MTCT rates remain well above the 5% elimination target in most sub-Saharan Africa countries. These countries require innovative strategies to scale-up their interventions to end paediatric HIV. We describe how the Elizabeth Glaser Paediatric AIDS Foundation (EGPAF) consortium and the Children's Investment Fund Foundation (CIFF) used the critical path method to facilitate rapid expansion and optimization of 2010 and 2013 WHO PMTCT guidelines to reduce Zimbabwe's MTCT rate from 22% in 2010 to 6.4% in 2015. Methods We analysed activities implemented and PMTCT programme data for the period before and during the EGPAF-CIFF project. The critical path method involved a cycle of collecting and analysing quarterly PMTCT indicator data and planning and implementing targeted activities to improve the PMTCT indicators. We performed a graphical trend analysis of data that measured availability of PMTCT services. Using Pearson's Chi2 test, we compared results of PMTCT uptake indicators at the start and end of the EGPAF-CIFF project and used regression discontinuity analysis to assess effectiveness of activities implemented to improve the PMTCT service uptake indicators. Results Zimbabwe rolled out WHO 2010 and 2013 PMTCT guidelines in less than 1 year during the EGPAF-CIFF project, yet it took more than 4 years to roll-out previous guidelines. All PMTCT indicators increased significantly (p < 0.001) comparing the five-year periods before and during the EGPAF-CIFF project. Critical path activities implemented increased five of the seven PMTCT uptake indicators. Conclusion Zimbabwe rapidly rolled-out and optimised new WHO PMTCT guidelines and drastically reduced its MTCT rate using the critical path method. We recommend wider use of the critical path method in public health programmes.